Preparation method of oxidized hydroxypropyl starch empty capsule

By combining hydroxypropylated starch with extrusion puffing technology, the environmental pollution and high cost problems in the preparation of oxidized starch are solved, low-energy consumption and high-efficiency starch modification are achieved, and oxidized hydroxypropyl starch hollow capsules suitable for industrial production are prepared with excellent mechanical properties and environmental protection characteristics.

CN120605254APending Publication Date: 2025-09-09JIANGNAN UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510768314.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-10
Publication Date
2025-09-09

AI Technical Summary

Technical Problem

Existing methods for preparing oxidized starch have problems such as environmental pollution, high cost, complex process and unsuitability for large-scale industrial application, especially the generation of acidic liquid and high energy consumption during the preparation of oxidized modified starch.

Method used

Hydroxypropylated starch is combined with extrusion puffing technology to precisely control the moisture content, effective chlorine concentration and screw speed to reduce starch viscosity. Oxidative modification is combined with extrusion puffing to form hydrogen bonds to enhance the structural integrity of the polymer matrix and prepare oxidized hydroxypropyl starch hollow capsules.

Benefits of technology

A low-energy, environmentally friendly starch modification method has been achieved, which improves the solubility and film properties of starch and is suitable for large-scale industrial production. The prepared oxidized hydroxypropyl starch hollow capsules have good tensile strength and elongation at break, meeting the preparation requirements of hard capsules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120605254A_ABST
    Figure CN120605254A_ABST
Patent Text Reader

Abstract

The invention relates to an oxidized hydroxypropyl starch empty capsule, and belongs to the technical field of capsules. The adhesive comprises the following main components: oxidized hydroxypropyl starch, a plasticizer, a gelling agent, a gelling aid and water. The starch viscosity can be effectively reduced, the gelling characteristic and stability can be optimized, and the dispersing and dissolving capacity of starch molecules in water can be enhanced by accurately controlling key process parameters such as the moisture content of materials and the effective chlorine addition amount in the extrusion process. In the dry oxidation treatment, carboxyl and carbonyl and hydroxyl in amylose and amylopectin molecules form hydrogen bonds, so that the structural integrity of a polymer matrix is improved, and the tensile strength and flexibility of the film are further improved. After the starch and the colloid are compounded, the gel temperature is moderate, and the stability of the system can be maintained. The hard capsule product provided by the invention has excellent mechanical properties, low friability and efficient disintegration performance. The preparation process simplifies the production process, reduces the cost, is green and environment-friendly, and has remarkable market application potential and wide popularization value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of capsule manufacturing, and more specifically relates to a method for preparing oxidized hydroxypropyl starch hollow capsules. Background Art

[0002] Capsules have a history of over 160 years and are now widely used in pharmaceuticals and health supplements. Gelatin, with its excellent biocompatibility and physicochemical properties, is the primary raw material for capsule production. However, gelatin capsules are relatively expensive and have several recognized drawbacks, such as their animal-derived nature, the risk of cross-linking with aldehyde-containing drugs, and gelatin's water instability. This has prompted the use of alternatives. An ideal gelatin substitute should possess at least some of gelatin's key properties, such as good film-forming properties, high solubility in water (>20%), low viscosity, and thermoreversibility. In the pharmaceutical market, plant-based capsules made from bio-based materials are one of the fastest-growing product categories. Numerous patents and literature reports exist on plant-based capsules, such as hydroxypropyl methylcellulose (HPMC), pullulan, and alginic acid. Compared to traditional gelatin hard capsules, plant-based capsules offer advantages such as wide adaptability, no cross-linking risk, and high stability. However, only a few of these products have achieved commercial application due to their high cost and the need for new processing facilities or conditions. Therefore, the development of non-gelatin capsules that are more affordable and can utilize conventional processing facilities is of great scientific and commercial significance.

[0003] Starch is a natural polysaccharide with advantages such as widespread availability, good renewability, good biodegradability, and low cost, particularly its excellent film-forming properties. Therefore, starch has gradually become a preferred choice for plant-based capsule research. However, starch-based materials still suffer from the disadvantages of poor mechanical properties and moisture resistance. However, the presence of a large number of active hydroxyl groups on the starch surface makes it suitable for the preparation of modified starch. Modified starches have better physical and chemical properties than their natural counterparts, and are therefore attracting increasing attention.

[0004] Common starch modification methods include physical, chemical, and biological modification. Chemical modification, a method that uses various chemical reagents to react with starch to alter its physical and chemical properties, is widely used and effective, making it the most widely used starch modification method. Among the various chemical modification methods used in industrial production, oxidative modification is the most common technique, widely adopted due to its ease of operation and significant effectiveness.

[0005] However, existing oxidation preparation methods generate large amounts of highly acidic liquids during the production process. Direct discharge of these liquids into the environment can cause environmental pollution, contradicting current environmental protection principles. Furthermore, the relatively high production costs of existing oxidation preparation methods limit their application in large-scale industrial production. Therefore, developing a preparation method that is both energy-efficient, environmentally friendly, and economically viable has become a key technical issue that needs to be addressed by those skilled in the art.

[0006] Patent CN 116355109 A uses hydrogen peroxide to first oxidize the hydroxyl groups in starch into aldehyde groups, and then oxidizes the aldehyde groups into carboxyl groups using sodium hypochlorite. Although the amount of sodium hypochlorite used is greatly reduced, wastewater is still generated during the production process.

[0007] Patent CN 110128557 A uses dry oxidation of corn starch directly without adding water during the preparation of oxidized starch, which does not produce a liquid with a high acid concentration. However, the amount of hydrochloric acid required for the reaction is large and the reaction time is long, making it unsuitable for large-scale industrial production.

[0008] Patent CN 106074439 B uses a low-substituted starch acetate containing acetyl groups and processes it with other ingredients into capsules through specialized methods. While the patent mentions the capsules' high shell clarity and good storage stability, it does not disclose the capsules' mechanical properties or disintegration characteristics. Furthermore, the spray-drying pregelatinization process consumes significant energy, significantly increasing production costs.

[0009] Although the above-mentioned oxidative modification method can reduce the viscosity of starch within a certain range, its reaction process involves multiple complex chemical reactions, resulting in cumbersome process steps, long reaction cycle, high complexity of manufacturing process, and defects such as high cost and difficulty in control. In addition, these patents all mention the application performance of capsules, which limits the large-scale promotion and application of this technical solution. Summary of the Invention

[0010] To address the shortcomings of existing starch capsule materials, we chose to use hydroxypropylated starch to improve film performance. Compared with natural starch, films made from hydroxypropylated starch are easier to prepare because the temperature required for dissolution is lower. In addition, this material performs well in packaging applications, especially its transparency and flexibility have been significantly improved. The production process of hydroxypropylated starch involves etherifying natural starch with propylene oxide in an alkaline environment. The introduction of hydroxypropylated starch not only enhances its hydrophilicity, but also causes a certain degree of destruction and weakening of the chemical bonds within the starch granules. This process helps to lower the gelatinization temperature and gelatinization viscosity of the starch, while improving the starch's swelling capacity, viscosity, solubility, and stability in repeated freeze-thaw cycles, ultimately improving the starch's transparency.

[0011] The present invention proposes a solution for preparing oxidized hydroxypropyl starch by an extrusion puffing method. The composite modified starch effectively weakens the starch's regeneration ability while introducing the hydrophilic group hydroxypropyl. By precisely controlling the oxidation conditions, such as moisture content and available chlorine concentration, the starch viscosity can be significantly reduced and its gelling properties can be optimized. The extrusion puffing process of the present invention has a high extrusion temperature, a fast screw speed, and a low moisture content, resulting in a significant puffing effect and a uniform reaction. The starch produced under these conditions is pregelatinized starch, which makes industrial capsule sol preparation faster and saves energy. The combination of oxidative modification and extrusion puffing treatment can enable the carboxyl and carbonyl groups in the oxidized starch to form hydrogen bonds with the hydroxyl groups in the amylose and amylopectin molecules, thereby enhancing the structural integrity of the polymer matrix and synergistically improving the tensile strength and elongation at break of the film, effectively overcoming the problem of high elongation at break but low tensile strength of the film prepared by wet oxidation treatment of hydroxypropyl starch, making the performance of the starch matrix more consistent with the preparation process requirements of traditional hollow hard capsules. Extrusion puffing combined with oxidative modification can loosen the starch gel network, provide a larger cavity, and accommodate more water molecules. The loose and uniform internal network structure can effectively improve the flexibility of the film.

[0012] The preparation process of the oxidized hydroxypropyl starch of the present invention is simple, rapid, efficient, and energy-efficient. The modified starch exhibits excellent properties, and the resulting pregelatinized starch is easily processed with a sol, offering promising prospects for industrial application and helping to reduce production costs. Films made from this starch exhibit both good tensile strength after extrusion and good elongation at break after oxidation, resulting in excellent overall performance. The preparation process of the oxidized hydroxypropyl starch does not produce acidic liquids, resulting in energy conservation, environmental protection, and pollution avoidance.

[0013] The first object of the present invention is to provide a method for preparing oxidized hydroxypropyl starch hollow capsules, comprising the following steps: A hydroxypropyl starch raw material having a hydroxypropyl content of 1%-2wt% is thoroughly mixed with a sodium hypochlorite aqueous solution containing 5-13wt% of available chlorine to obtain a mixture, which is then allowed to stand overnight to balance moisture, and the moisture content of the mixture is controlled to be 17%-23wt%. The balanced mixture is extruded through a twin-screw extruder, and the temperature in the final extrusion section is controlled to be 140-150°C and the screw speed is controlled to be 130-150 rpm. The extrudate is collected and placed in a 40°C forced air drying oven for drying and pulverization to obtain oxidized hydroxypropyl starch. The oxidized hydroxypropyl starch is then mixed and stirred with a plasticizer, a gelling agent, a coagulant aid, and water to obtain a composite. The composite is heated, kept warm, dipped in glue to form embryos, and dried to obtain oxidized hydroxypropyl starch hollow capsules.

[0014] In one embodiment, the hydroxypropyl starch raw material is one or more of hydroxypropylated tapioca starch, potato starch or sweet potato starch.

[0015] In one embodiment, the amount of sodium hypochlorite aqueous solution added is 0.2-1 wt % of the dry weight of starch.

[0016] In one embodiment, the mass of water required to add to make the moisture content of the mixture meet the requirement of 1-23 wt % is calculated based on the initial moisture content of the raw starch, and the corresponding mass of water is taken to dilute the sodium hypochlorite solution, and the diluted sodium hypochlorite solution is mixed with the starch.

[0017] In one embodiment, the amount of available chlorine added is 0.5 wt % of the dry weight of starch.

[0018] In one embodiment, the moisture content of starch is adjusted to 19%.

[0019] In one embodiment, the temperature in the final extrusion stage is 150°C.

[0020] In one embodiment, the screw speed is 130 rpm.

[0021] In one embodiment, the oxidized hydroxypropyl starch comprises 80-110 parts by weight, the plasticizer comprises 20-40 parts by weight, the gelling agent comprises 8-11 parts by weight, the coagulant aid comprises 0.08-0.11 parts by weight, and the water comprises 390-420 parts by weight.

[0022] In one embodiment, the plasticizer includes one or more of glycerin, sorbitol, and microcrystalline cellulose, the gelling agent includes one or more of κ-carrageenan and I-carrageenan, and the coagulant includes one or more of potassium chloride and sodium citrate.

[0023] In one embodiment, the added mass of the plasticizer glycerol is 15% of the mass of the dry basis of starch, and the added mass of the plasticizer sorbitol is 15% of the mass of the dry basis of starch.

[0024] In one embodiment, the gelling agent is at least one of κ-carrageenan and Ɩ-type carrageenan, and the added mass thereof is 5%-15% of the dry basis mass of starch, more preferably 10%.

[0025] In one embodiment, the coagulant aid is sodium citrate, and the addition amount thereof is 4-20 mmol / L, more preferably 10 mmol / L.

[0026] In one embodiment, the specific operations of heating the composite, keeping the temperature, dipping in glue to form embryos, and drying are as follows: heating the composite to a temperature of 90-100°C to completely dissolve the system to obtain a glue solution; dipping in glue to form films: maintaining the temperature at 60-70°C, degassing the glue solution, immersing the template for preparing capsules in the glue solution, dipping in glue to form films, and obtaining crude capsules; finally, drying the crude capsules at 25-50°C for 0.5-5 h, and then performing shelling, cutting, and sleeve-fitting processes to obtain oxidized hydroxypropyl starch hollow capsules.

[0027] The second object of the present invention is to provide oxidized hydroxypropyl starch hollow capsules prepared by the above method.

[0028] Beneficial effects: (1) By subjecting hydroxypropyl starch to extrusion oxidation and puffing treatment, the moisture content, effective chlorine concentration, extrusion screw speed and extrusion screw temperature of the starch can be precisely controlled during the extrusion and puffing process, thereby effectively reducing the disintegration value and regeneration value of the starch, thereby effectively inhibiting the aging trend of the starch, allowing the starch to maintain a high stability during heating and stirring, and significantly reducing the viscosity of the starch, achieving the characteristics of "high concentration and low viscosity".

[0029] (2) After the starch is pre-gelatinized by extrusion, the solubility and rehydration ability of the modified starch molecules and their dispersibility in the system are improved, so that they can dissolve and gel more quickly, enhance the stability of the system, and improve the uniformity of the rubber.

[0030] (3) During the dry oxidation process, carboxyl and carbonyl groups can form hydrogen bonds with the hydroxyl groups in the amylose and amylopectin molecules, giving the polymer matrix better structural integrity and thus improving the tensile strength of the film; the network structure of the modified starch gel becomes loose, forming a larger cavity to accommodate more water molecules, and its loose and uniform internal network structure can effectively improve the flexibility of the film; the modified starch gel has a stronger binding capacity for water and lower fluidity. The sample contains more bound water, and during the cooling process, a relatively large amount of water is trapped in the gel network.

[0031] (4) Oxidized hydroxypropyl starch hollow capsules do not contain gelatin, have stable chemical properties, no cross-linking reaction, and high safety, which improves the storage stability of the drug; they are green and safe, and the preparation method is efficient, fast, and low-consumption, which is conducive to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The hard capsule prepared by using oxidized hydroxypropyl starch in the present invention

[0033] Figure 2 The shear viscosity of the starch prepared in Examples 1-4 is

[0034] Figure 3 The shear viscosity of the starch prepared in Examples 5-7 is

[0035] Figure 4 Scanning electron microscopy images of starch gels in Example 1 and Comparative Example 1

[0036] Figure 5 Starch gel moisture distribution diagram of Example 1 and Comparative Example 1 DETAILED DESCRIPTION

[0037] The following describes preferred embodiments of the present invention. It should be understood that the embodiments are for better explanation of the present invention and are not intended to limit the present invention.

[0038] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or those recommended by the manufacturer. All reagents or instruments used, if the manufacturer is not specified, are commercially available conventional products.

[0039] Test method: Determination of the short-range order of oxidized hydroxypropyl starch by infrared spectroscopy (FTIR): The short-range order of starch was determined using a Fourier transform infrared spectrometer (FTIR). The sample was accurately weighed and mixed with potassium bromide at a ratio of 1:60 (m:m, dry basis). 60 mg of the carefully ground mixture was pressed into a thin sheet and scanned in FT-IR transmission mode. Air background was subtracted and the measurement range was 400-4000 cm -1 , resolution 4 cm -1 The Omnic software was used to analyze the wavelengths of 800-1200 cm -1 The Fourier self-deconvolution process was performed on the area, and the half-peak width and enhancement factor were set to 18 cm -1 and 2.6, calculate 1045 cm -1 / 1022 cm -1 The peak intensity ratio.

[0040] Determination of the Gelatinization Properties of Hydroxypropyl Oxide Starch: The gelatinization properties of the sample were determined using a rapid viscometer. Weigh 5g of starch sample and mix with deionized water in an RVA aluminum container to prepare a 20% (w / w, dry basis) starch solution. The gelatinization properties of the sample were determined.

[0041] Adhesive viscosity test: The adhesive viscosity was measured using a rheometer. The mold type was parallel plate / parallel plate, the mold diameter was 40 mm, and the gap was 1 mm. The test temperature was set to 50 °C, and the linear shear rate change mode was used. The shear rate was varied from 0.1s to -1 Increase to 100 s -1 .

[0042] Preparation of starch film: Composite modified starch-based film was prepared by the cast film method. The preparation process is as follows: prepare 20% (w / w, db) starch emulsion, gelatinize in a boiling water bath for 30 minutes, transfer to a 60°C water bath for insulation and degassing treatment for 30 minutes, pour the sample into a 150mm×150mm square culture dish and let it stand for 30 minutes, then blow dry at 40°C for 2 hours. After drying, the sample is transferred to a constant temperature and humidity chamber (relative humidity of 54%, temperature of 25°C) and let it stand for more than 72 hours for further testing.

[0043] Gel Temperature Test: The gel temperature of the adhesive was measured using a rheometer. A 40 mm parallel plate measuring system was used, with a frequency of 1 Hz, a strain of 3%, and a parallel plate spacing of 1 mm. The temperature was cooled from 90°C to 20°C at a rate of 5°C / min, allowed to equilibrate for 3 minutes, and then raised to 90°C at a rate of 5°C / min. The changes in G′ and G″ during the cooling and heating processes were recorded. The curve where these two curves intersected was the gel temperature of the adhesive.

[0044] Gel microstructure observation: The starch gel was freeze-dried, and approximately 1 mm cubes were cut from the dry preparation and affixed to the microscope stage using a disc made of carbon tape. The sample was then sputter-coated with gold using a sputter coater and imaged using a scanning electron microscope at an accelerating voltage of 5 kV.

[0045] Film tensile strength and elongation at break were measured using a texture analyzer. The film was cut into 1 × 8 cm strips, and the thickness was measured at eight random points on the strip using a micrometer. The average value was calculated.

[0046] The mechanical properties of the membrane were measured using a physical property analyzer equipped with a pulling fixture. The distance between the upper and lower clamps was fixed at 50 mm and the pulling speed was 0.5 mm / s.

[0047] Test of tightness and disintegration time of hollow hard capsules: For tightness test, take 10 capsules, pinch the two ends of the capsules lightly with the thumb and index finger, rotate and pull them apart, there should be no adhesion, deformation or rupture, then fill them with talcum powder, lock the cap and body, and drop them one by one from a height of 1 m onto a wooden board with a thickness of 2 cm. There should be no powder leakage; if there is a small amount of powder leakage, it should not exceed 2 capsules. If it exceeds, take another 10 capsules for retesting, and all should meet the requirements.

[0048] Disintegration time test: Take 6 capsules of this product, fill them with talcum powder, and test them according to the method under the disintegration time test method (General Rule 0921) for capsules, with a baffle. Each capsule should disintegrate within 10 minutes, and all capsules except the broken capsule shell should pass through the sieve.

[0049] If there are capsule shell fragments that cannot pass through the screen, but have softened and adhered to the screen and baffle, they can be considered to meet the requirements. If one capsule does not meet the requirements, another 6 capsules should be retested, and all should meet the requirements.

[0050] Example 1

[0051] A method for preparing oxidized hydroxypropyl starch hollow capsules comprises the following steps:

[0052] (1) Preparation of oxidized hydroxypropyl starch:

[0053] First, according to the water content wt% of the raw material hydroxypropyl tapioca starch itself, the mass of water required to adjust the starch water content to 19wt% is calculated. Water is weighed and used to dilute the sodium hypochlorite solution. The effective chlorine addition amount is 0.2wt% of the dry weight of the starch. The hydroxypropyl starch is thoroughly mixed with the diluted sodium hypochlorite solution and left to stand overnight in a ziplock bag to balance the moisture. The hydroxypropyl starch raw material after moisture balance is extruded under the following extrusion conditions, wherein the extrusion temperature is: 50°C in zone 1, 60°C in zone 2, 110°C in zone 3, and 150°C in zone 4; the screw speed is 130rpm, and the feed speed is 5.2rpm. The extrudate is collected and placed in a 40°C forced air drying oven to dry for 24 hours, crushed and passed through a 100-mesh sieve for standby use to obtain oxidized hydroxypropyl starch 1.

[0054] (2) Preparation of empty capsules:

[0055] First, 100 parts by mass of oxidized hydroxypropyl starch, 15 parts by mass of glycerol, 15 parts by mass of sorbitol, 10 parts by mass of κ-carrageenan, 0.3725 parts by mass of potassium chloride, 2 parts by mass of microcrystalline cellulose, and 400 parts by mass of water are mixed, stirred evenly, and heated to a temperature of 100°C to completely dissolve the system to obtain a glue solution, wherein the oxidized hydroxypropyl starch is prepared by the method described in the first aspect of step (1); dipping in glue and making a film: maintaining the temperature at 70°C, degassing the glue solution, immersing the template for preparing capsules in the glue solution, dipping in glue and making a film to obtain a crude capsule product; finally, drying the crude capsule product at 40°C for 2h, and then performing shelling, cutting, and sleeve processing to obtain an oxidized hydroxypropyl starch capsule. The hard capsule prepared by using oxidized hydroxypropyl starch in the present invention is as follows: Figure 1 .

[0056] Example 2

[0057] The moisture content of the hydroxypropyl starch in step (1) of Example 1 was adjusted to 19 wt %, and the amount of available chlorine added was 0.5 wt % of the dry weight of the starch. Other conditions remained the same as in Example 1 to obtain oxidized hydroxypropyl starch hollow capsules.

[0058] Example 3

[0059] The moisture content of the hydroxypropyl starch in step (1) of Example 1 was adjusted to 19 wt %, and the amount of available chlorine added was adjusted to 0.7 wt % of the dry weight of the starch. Other conditions remained the same as in Example 1 to obtain oxidized hydroxypropyl starch capsules.

[0060] Example 4

[0061] The moisture content of the hydroxypropyl starch in step (1) of Example 1 was adjusted to 19 wt %, and the amount of available chlorine added was 1.0 wt % of the dry weight of the starch. Other conditions remained the same as in Example 1 to obtain oxidized hydroxypropyl starch capsules.

[0062] Example 5

[0063] The moisture content of the hydroxypropyl starch in step (1) of Example 1 was adjusted to 17 wt %, and the amount of available chlorine added was 0.5 wt % of the dry weight of the starch. The extrusion conditions in step (1) of Example 1 were adjusted to the following: the extrusion temperature was 50° C. in zone 1, 60° C. in zone 2, 110° C. in zone 3, and 150° C. in zone 4. Other conditions remained the same as in Example 1, to obtain oxidized hydroxypropyl starch capsules.

[0064] Example 6

[0065] The moisture content of the hydroxypropyl starch in step (1) of Example 1 was adjusted to 21 wt %, and the amount of available chlorine added was adjusted to 0.5 wt % of the dry weight of the starch. The extrusion conditions in step (1) of Example 1 were adjusted to the following: the extrusion temperature in zone 1 was 50° C., the temperature in zone 2 was 60° C., the temperature in zone 3 was 110° C., and the temperature in zone 4 was 150° C.; other conditions remained the same as in Example 1, to obtain oxidized hydroxypropyl starch capsules.

[0066] Example 7

[0067] The moisture content of the hydroxypropyl starch in step (1) of Example 1 was adjusted to 23 wt %, and the amount of available chlorine added was 0.5 wt % of the dry weight of the starch. The extrusion conditions in step (1) of Example 1 were adjusted to the following: the extrusion temperature was 50° C. in zone 1, 60° C. in zone 2, 110° C. in zone 3, and 150° C. in zone 4. Other conditions remained the same as in Example 1, to obtain oxidized hydroxypropyl starch capsules.

[0068] Test example:

[0069] To evaluate the practical application performance of oxidized hydroxypropyl starch, this example tested the short-range order and gelatinization properties of the resulting oxidized hydroxypropyl starch, as well as the viscosity of the starch-containing gelatin solution, the gel temperature of the starch paste, the mechanical properties of the starch film (including tensile strength and elongation at break), and the friability and disintegration properties of the resulting oxidized hydroxypropyl starch hollow capsules. The test results are shown in Tables 1, 2, and 3.

[0070] The rheological shear test of starch glue was carried out, and the results were as follows: Figure 2 , Figure 3 As shown in the figure, when the moisture content of starch is controlled to be constant, the shear viscosity tends to decrease with the increase of the amount of available chlorine added. This is mainly because sodium hypochlorite preferentially attacks the non-crystalline area of ​​starch, generates carboxyl or carbonyl groups by oxidizing the C2, C3 and C6 hydroxyl groups of the glucose unit, and is accompanied by the cleavage of the glycosidic bond. The higher the concentration, the more obvious the destruction effect. When the amount of available chlorine added to starch is controlled to be constant, the moisture content of starch during extrusion is increased, and it is found that the shear viscosity of starch tends to increase. This is because during extrusion and puffing, water acts as a plasticizer to reduce the interaction force between starch molecules, making the starch less likely to be destroyed. Therefore, choosing the appropriate moisture content and available chlorine addition is very important when preparing oxidized hydroxypropyl starch.

[0071] After the oxidized hydroxypropyl starch is compounded with the colloid, the gelation temperature is moderate, resulting in starch-based films with high tensile strength and good hollow capsule disintegration properties. As shown in Table 1, precise control of extrusion conditions, including screw temperature, screw speed, available chlorine concentration, and starch moisture content, significantly reduces starch viscosity and optimizes its gelation properties. Further research has shown that films prepared from hydroxypropyl starch treated by extrusion have significantly enhanced tensile strength.

[0072] The hydroxypropylated tapioca starch (Examples 1-7) after oxidation treatment showed R in the infrared spectrum. 1045 / 1022 The values ​​(Table 2) are all higher than those of raw cassava starch, indicating that its short-range order is significantly improved. This order enables the starch to build a more ordered network structure during gel formation, enhancing gel strength, while also improving the water holding capacity of the capsule material and reducing the tendency of starch to retrogradation.

[0073] Scanning electron microscope images show ( Figure 4 ), the starch gel network after dry oxidation treatment has a loose structure with large cavities that can accommodate more water molecules. Its uniform internal network structure can improve the flexibility of the film. The gel moisture distribution image shows ( Figure 5 ), extrusion puffing treatment combined with oxidation has stronger binding capacity to water than simple extrusion hydroxypropyl modification, lower fluidity, and the sample contains more bound water. During the cooling process, relatively more water is trapped in the gel network.

[0074] In addition, with the increase of available chlorine content, R 1045 / 1022 The values ​​showed an upward trend, indicating that moderate oxidation helps to enhance the short-range order of starch. The gelatinization characteristics analysis showed (Table 3) that the oxidized cassava hydroxypropyl starch showed lower disintegration and retrogradation values, indicating that the starch retrogradation phenomenon was suppressed.

[0075] Table 1 Application performance of hydroxypropyl starch under different extrusion oxidation conditions

[0076]

[0077]

[0078] Table 2 Infrared short-range ordering of hydroxypropyl starch under different extrusion oxidation conditions

[0079]

[0080] Table 3 Gelatinization characteristics of hydroxypropyl starch under different extrusion oxidation conditions

[0081]

[0082] Comparative Example 1

[0083] First, based on the wt% water content of the raw hydroxypropyl tapioca starch itself, calculate the mass of water required to adjust the starch moisture content to 19 wt%. Weigh the water, thoroughly mix the hydroxypropyl tapioca starch with the weighed water, and let it stand overnight in a ziplock bag to equilibrate the moisture. The remaining steps remain the same as in Example 1.

[0084] In order to investigate the practical application performance of hydroxypropyl starch after simple extrusion, this comparative example measured the viscosity of the glue prepared by extruding hydroxypropyl starch, the mechanical properties (tensile strength, elongation at break) of the starch film prepared by extruding hydroxypropyl starch, and the friability and disintegration properties of the prepared hollow capsules. As well as the friability and disintegration properties of the extruded hydroxypropyl starch hollow capsules prepared in step (2). The test results are shown in Table 4.

[0085] Film samples made from extruded hydroxypropyl starch exhibited high tensile strength but relatively low elongation at break. This is because increasing screw speed typically increases shear forces on the starch within the extruder. This increased shear force facilitates interaction between starch molecules, promoting molecular chain alignment and partial recrystallization, thereby improving the tensile strength of the starch film. Furthermore, higher screw speeds increase the degree of starch plasticization, allowing the starch molecules to flow and rearrange more easily during extrusion, which helps improve film uniformity and tensile strength. Compared to films made with oxidized hydroxypropyl starch, this film exhibited higher tensile strength, but still had lower elongation at break, and the viscosity of the adhesive was higher, which made film preparation more challenging. Furthermore, the films produced were thicker than those made with oxidized hydroxypropyl starch. The gelation temperature of hydroxypropyl starch extruded alone was relatively low compared to that of oxidized hydroxypropyl starch, making it difficult to coat the film. Therefore, the addition of sodium hypochlorite during extrusion is necessary to optimize film properties and reduce the difficulty of capsule preparation.

[0086] Table 4

[0087]

[0088] Comparative Example 2

[0089] The oxidation treatment of hydroxypropyl starch in step (1) of Example 3 was omitted, and the hydroxypropyl starch in step (1) was subjected to wet oxidation treatment instead. The specific operation was as follows: First, an appropriate amount of hydroxypropyl starch was accurately weighed and mixed with deionized water to prepare a starch milk with a mass fraction of 40% (w / w, db), and the starch milk was placed in a four-necked flask. The water bath temperature was set to 25°C and stirred continuously. A sodium hypochlorite solution with an effective chlorine content of 0.5% (based on the mass percentage of absolute dry starch) was slowly added using a constant pressure funnel while continuously stirring the starch milk. After the reaction started, a pH meter was used to monitor the pH value of the system in real time, and during the reaction, 10% (m / m) hydrochloric acid was used to accurately control the pH value and stabilize it in the range of 8.3 to 8.5. The time for adding the sodium hypochlorite solution should be strictly controlled to about 1.5 hours. Subsequently, a saturated sodium bisulfite solution was added for a reduction reaction to remove residual chlorine. The product was then washed with water and dried at 40°C. The dried product was then pulverized and passed through a 100-mesh sieve to produce wet-oxidized hydroxypropyl starch. Aside from the wet oxidation treatment, the remaining steps were the same as in Example 1.

[0090] To investigate the practical application performance of wet-oxidized hydroxypropyl starch, this comparative example measured the viscosity of a glue solution prepared using wet-oxidized hydroxypropyl starch and the mechanical properties (tensile strength and elongation at break) of a starch film prepared using wet-oxidized hydroxypropyl starch. The test results are shown in Table 5.

[0091] The film samples made of wet-oxidized hydroxypropyl starch have a high elongation at break but a low tensile strength, which cannot meet the tensile strength required by hard capsules. This is because, during the wet preparation process, starch is dispersed in water, the oxidant can fully contact the starch granules, the reaction is more uniform, and the degree of oxidation of the starch molecular chains is more consistent. This helps to form a more uniform film structure, reduce stress concentration points caused by uneven oxidation, and thus improve the elongation at break of the film. To this end, the oxidative modification combined with extrusion puffing treatment is selected to effectively improve the tensile strength of the film and to a certain extent improve the elongation at break of the film.

[0092] Table 5

[0093]

[0094] Comparative Examples 3-12

[0095] The preparation method of Example 3 was used with the exception that the amount of available chlorine added, the starch moisture content, the extrusion temperature, and the screw speed were regulated to prepare oxidized hydroxypropyl starch. The viscosity of the glue prepared from the oxidized hydroxypropyl starch of this comparative example in step (1), the mechanical properties (tensile strength and elongation at break) of the starch film prepared from the oxidized hydroxypropyl starch of this comparative example, and the friability and disintegration properties of the oxidized hydroxypropyl starch hollow capsules prepared in step (2) of this comparative example were measured. The test results are shown in Table 6.

[0096] Table 6 Effects of material moisture, available chlorine addition, screw speed and extrusion temperature on the application performance of oxidized hydroxypropyl starch

[0097]

[0098] Note: “-” means no result was detected.

[0099] After in-depth research, the present invention found that in the process of preparing hollow capsules, the viscosity of the glue solution needs to be strictly controlled between 200mPa·s and 1000mPa·s. By comparing the results of Comparative Examples 3-12 with those of Examples 1-7, it can be clearly seen that only when the material moisture is maintained at 17%-23%wt%, the available chlorine content is between 0.2%-1%, the extrusion temperature is stable at 140℃-150℃, the screw speed is maintained at 120rpm-150rpm, and the hydroxypropyl starch hydroxypropyl content is between 1%-2%, can the oxidized hydroxypropyl starch prepared by the present invention simultaneously achieve the following properties, fully meeting the requirements of the hollow capsule preparation process: the viscosity of the prepared glue solution can be kept stable within the range of 200mPa·s to 1000mPa·s; the film tensile strength is not less than 30MPa, and the film elongation at break is not less than 10%; the surface of the prepared hard capsule is smooth and neat, the friability is 0, and the disintegration time is controlled within 10min. On the other hand, if the moisture content of the material is too high, the extrusion temperature is too low, the screw speed is too low, or the amount of effective chlorine added exceeds the appropriate range (too high or too low), it will be difficult to control the viscosity of the gelatin within the ideal range of 200mPa·s to 1000mPa·s, which will affect the smooth progress of the hard capsule preparation process and make it difficult to successfully prepare qualified hollow capsule products with a neat and smooth surface, no leakage, and friability and disintegration time that meet the standards.

[0100] It can be seen that the oxidized hydroxypropyl starch prepared by the present invention after optimizing parameters based on a specific process has many advantages in preparing starch films. During dry oxidation, the carboxyl and carbonyl groups can form hydrogen bonds with the hydroxyl groups in the amylose and amylopectin molecules, giving the polymer matrix better structural integrity, thereby improving the tensile strength of the film; the network structure of the modified starch gel becomes loose, forming a larger cavity to accommodate more water molecules, and its loose and uniform internal network structure can effectively improve the flexibility of the film; the modified starch gel has a stronger binding property to water and a lower fluidity. The sample contains more bound water. During the cooling process, relatively more water is trapped in the gel network, which improves the elongation at break of the film.

[0101] This process can effectively control the viscosity of starch glue, achieve the characteristics of "high concentration and low viscosity", improve the gel properties of the glue, and give the starch film better mechanical properties. The elongation at break is significantly improved, and the capsule shell is not easy to break, making it more in line with the requirements of the hard capsule preparation process.

[0102] Although the present invention has been disclosed above in terms of preferred embodiments, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing oxidized hydroxypropyl starch hollow capsules, characterized in that: The following steps are involved: A hydroxypropyl starch raw material containing 1% to 2% by weight of hydroxypropyl groups is thoroughly mixed with a sodium hypochlorite aqueous solution containing 5 to 13% by weight of available chlorine to obtain a mixture, which is then allowed to stand overnight to balance moisture, and the moisture content of the mixture is controlled to be 17% to 23% by weight. The balanced mixture is extruded through a twin-screw extruder, and the temperature in the final extrusion section is controlled to be 140 to 150° C., and the screw speed is controlled to be 130 to 150 rpm. The extrudate is collected and placed in a 40° C. forced air drying oven for drying and pulverization to obtain oxidized hydroxypropyl starch. The oxidized hydroxypropyl starch is then mixed and stirred with a plasticizer, a gelling agent, a coagulant aid, and water to obtain a composite. The composite is heated, kept warm, dipped in glue to form embryos, and dried to obtain oxidized hydroxypropyl starch hollow capsules.

2. The method for preparing the oxidized hydroxypropyl starch hollow capsules according to claim 1, characterized in that: The hydroxypropyl starch raw material is one or more of hydroxypropylated tapioca starch, potato starch or sweet potato starch.

3. The method for preparing the oxidized hydroxypropyl starch hollow capsules according to claim 1, wherein: The amount of effective chlorine added is 0.2-1 wt% of the dry weight of starch.

4. The method for preparing the oxidized hydroxypropyl starch hollow capsules according to claim 1, wherein: Based on the initial moisture content of the raw starch, the mass of water required to add when the moisture content of the mixture meets the requirement of 1-23wt% is calculated, the corresponding mass of water is taken to dilute the sodium hypochlorite solution, and the diluted sodium hypochlorite solution is mixed with the starch.

5. The method for preparing oxidized hydroxypropyl starch hollow capsules according to claim 1, characterized in that: The oxidized hydroxypropyl starch comprises 80-110 parts by weight, a plasticizer 20-40 parts by weight, a gelling agent 8-11 parts by weight, a coagulant aid 0.08-0.5 parts by weight, and water 390-420 parts by weight.

6. The method for preparing oxidized hydroxypropyl starch hollow capsules according to claim 5, characterized in that: The plasticizer includes one or more of glycerin, sorbitol, and microcrystalline cellulose; the gelling agent includes one or more of κ-carrageenan and I-carrageenan; and the coagulant aid includes one or more of potassium chloride and sodium citrate.

7. The method for preparing oxidized hydroxypropyl starch hollow capsules according to claim 5, characterized in that: The specific operations of heating the composite material, keeping the temperature, dipping in glue to form embryos, and drying are as follows: heating the composite material to a temperature of 90-100° C. to completely dissolve the system to obtain glue solution; dipping in glue to form films: maintaining the temperature at 60-70° C., degassing the glue solution, immersing the template for preparing capsules in the glue solution, dipping in glue to form films, and obtaining crude capsules; finally, drying the crude capsules at 25-50° C. for 0.5-5 hours, and then performing shelling, cutting, and sleeve-fitting processes to obtain oxidized hydroxypropyl starch hollow capsules.

8. Oxidized hydroxypropyl starch hollow capsules prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • A method for preparing hydroxypropyl starch capsules

    CN106074439B

  • Oxidized starch and preparation method thereof

    CN110128557A